2007
DOI: 10.1209/0295-5075/81/17002
|View full text |Cite
|
Sign up to set email alerts
|

Complementarity of perturbations driving insulator-to-metal transition in a charge-ordered manganite

Abstract: Modulation of charge carrier dynamics and hence electrical conductivity of solids by photoexcitation has been a rich field of research with numerous applications. Similarly, electric and magnetic field assisted enhancement of conductivity are of fundamental importance and technological use.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Clearly, the heating curve of the phototransformed state is similar to the heating curve for samples with y < 0.45 (see figure 1) all of which exhibit an MI transition at T MI C , the value of which decreases with increasing y. A similar effect induced by pulsed laser irradiation has already been demonstrated [34]. The above observation can be explained only in terms of a photo-induced collapse of the COI state into a metallic state, which is presumably FM.…”
Section: Introductionsupporting
confidence: 74%
See 3 more Smart Citations
“…Clearly, the heating curve of the phototransformed state is similar to the heating curve for samples with y < 0.45 (see figure 1) all of which exhibit an MI transition at T MI C , the value of which decreases with increasing y. A similar effect induced by pulsed laser irradiation has already been demonstrated [34]. The above observation can be explained only in terms of a photo-induced collapse of the COI state into a metallic state, which is presumably FM.…”
Section: Introductionsupporting
confidence: 74%
“…Although the explicit signature of charge ordering is absent in our R-T measurements, electron diffraction experiments on the y = 0.275 sample clearly show the onset of charge ordering at 210 K [29]. The intrinsic IMT is also a sensitive function of applied magnetic and electric fields, and a complementarity of these externally applied perturbations has been reported for films with y = 0.45 [34]. For the y = 0.45 sample, electric fields of strength ≈0.6 and 10 kV cm −1 induce IMT at 30 and 80 K respectively, while the maximum bias field strength for the samples in figure 1 was less than 0.07 kV cm −1 .…”
Section: Introductionmentioning
confidence: 49%
See 2 more Smart Citations
“…The original state can be recovered only by heating. PPC phenomena have been observed in metallic ͑mostly oxygen deficient͒ [7][8][9][10][11] and in insulating charge-ordered 12,13 ͑CO͒ manganites. Since the effect is often observed in oxygen-deficient samples, it was suggested that the underlying mechanism might be similar as in oxygen-deficient YBa 2 Cu 3 O 7−␦ thin films ͑Ref.…”
Section: Introductionmentioning
confidence: 99%